2019
DOI: 10.3390/diagnostics9010029
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Pulmonary Nodule Detection Applying Deep Learning or Machine Learning Algorithms to the LIDC-IDRI Database: A Systematic Review

Abstract: The aim of this study was to provide an overview of the literature available on machine learning (ML) algorithms applied to the Lung Image Database Consortium Image Collection (LIDC-IDRI) database as a tool for the optimization of detecting lung nodules in thoracic CT scans. This systematic review was compiled according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Only original research articles concerning algorithms applied to the LIDC-IDRI database were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 47 publications
(100 reference statements)
2
52
2
1
Order By: Relevance
“…Several other studies have trained and tested deep learning algorithms on the large, publicly accessible LIDC-IDRI database [16] and, recently, a systematic review was published overviewing the different studies that have tested on this database [50]. However, to review deep learning performance it is also necessary to review studies that did not use the LIDC-IDRI, as CT scans may vary from region to region.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have trained and tested deep learning algorithms on the large, publicly accessible LIDC-IDRI database [16] and, recently, a systematic review was published overviewing the different studies that have tested on this database [50]. However, to review deep learning performance it is also necessary to review studies that did not use the LIDC-IDRI, as CT scans may vary from region to region.…”
Section: Discussionmentioning
confidence: 99%
“…There were 135 papers duplicated between these two categories. Two systematic reviews were identified [18,19]. Given the narrative nature of this review, the final cohort of papers was hand-picked to provide the reader with the best general overview of the topic and was not meant to be comprehensive.…”
Section: Methods Of Literature Selectionmentioning
confidence: 99%
“…There are algorithms that assist with the detection, per se, of nodules (computer-aided detection or CAD), and those that assist with specific diagnosis (computeraided diagnosis or CADx) [25]. The extent of the work in CAD is reflected in the 2019 systematic [18]. There has also been extensive research into CADx, where the usual goal is to develop models that can distinguish between benign and malignant lesions based on imaging.…”
Section: Analyzing Chest Imagingmentioning
confidence: 99%
“…Die Detektion von Lungenrundherden kann weiter verbessert werden, wenn zum Lernen neuronale Netzwerke (Convolutional Neural Network, ConvNet) herangezogen werden. Mit Hilfe von ConvNets lässt sich eine Genauigkeit von 82,2-97,6 % bei einer Sensitivität von 83,1-96,6 % und einer Spezifität von 71,4-98,2 % erreichen [26].…”
Section: Detektion Pulmonaler Rundherdeunclassified